2016
DOI: 10.1093/cid/ciw806
|View full text |Cite
|
Sign up to set email alerts
|

From Care to Cure: Demonstrating a Model of Clinical Patient Navigation for Hepatitis C Care and Treatment in High-Need Patients

Abstract: The NYC Department of Health implemented a patient navigation program, Check Hep C, to address patient and provider barriers to HCV care and potentially lifesaving treatment. Services were delivered at two clinical care sites and two sites that linked patients to off-site care. Working with a multidisciplinary care team, patient navigators provided risk assessment, health education, treatment readiness and medication adherence counseling, and medication coordination. Between March 2014 and January 2015, 388 pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
55
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(56 citation statements)
references
References 23 publications
1
55
0
Order By: Relevance
“…Studies formally evaluating this approach are ongoing. Numerous outreach programmes have been designed, particularly in large urban centres, with initial data supporting the use of peer navigators to assist with linkage to and retention in care, provision of care by nurses and primary care physicians rather than specialists, and integration of HCV treatment into multidisciplinary care to address other health and social issues 102,103 . Initial results suggest that such models are effective, with cure rates comparable to or better than those seen in clinical trials and real-world cohorts treated in hepatology and infectious disease clinics 96 .…”
Section: Cascade Of Care and Improving Care Models For Hcv [H4]mentioning
confidence: 99%
“…Studies formally evaluating this approach are ongoing. Numerous outreach programmes have been designed, particularly in large urban centres, with initial data supporting the use of peer navigators to assist with linkage to and retention in care, provision of care by nurses and primary care physicians rather than specialists, and integration of HCV treatment into multidisciplinary care to address other health and social issues 102,103 . Initial results suggest that such models are effective, with cure rates comparable to or better than those seen in clinical trials and real-world cohorts treated in hepatology and infectious disease clinics 96 .…”
Section: Cascade Of Care and Improving Care Models For Hcv [H4]mentioning
confidence: 99%
“…Adherence among patients with chronic HCV infection and comorbid psychiatric disorders remains a concern despite the advent of IFN‐free DAA treatments. Lower adherence is hypothesized due to cases of severe, untreated psychiatric disorders and higher rates of comorbid substance use disorders ; however, DAA regimens have shown similarly high adherence rates in clinical trials among patient populations traditionally considered to be at‐risk for nonadherence including patients with psychiatric disorders, people who inject drugs and patients on stable opioid substitution therapy . In its clinical trial programme, overall adherence to G/P regimens has been reported at >95% with comparable rates among patients with psychiatric disorders, people who inject drugs and patients on stable opioid substitution therapy .…”
Section: Discussionmentioning
confidence: 99%
“…Based on these data, recent HCV treatment guidelines recommend DAA regimens without any restrictions based on psychiatric comorbidities . However, there has been more limited use of DAAs in patients with psychiatric disorders in both late phase trials and clinical practice potentially due to concerns about treatment adherence and drug–drug interactions (DDIs) with neuropsychiatric co‐medications . Thus, there is an unmet need to better understand the impact of psychiatric disorders on the treatment adherence, efficacy and safety of DAA regimens.…”
Section: Introductionmentioning
confidence: 99%
“…High-needs patients, including those with mental illness, substance use disorders, and/or a lack of social support, may face a variety of barriers to HCV care and treatment, including limited access to health care services and difficulties navigating the health care system (5,6). Care coordination programs addressing these barriers for chronic diseases have shown improved outcomes in similar populations (7,8).…”
Section: Discussionmentioning
confidence: 99%